Mechanical properties of concrete with 5 and 10 percent palm oil boiler stone (POBS) as fine aggregate replacement - Lee, Chooi Ying (2010)
Large quantities of wastes are produced from agro-based industries every year. With the enormous increase in the quantity of waste needing disposal and acute shortage of dumping sites, the use of these waste materials in construction industry would contribute towards a cleaner environment. On this matter, a study has been conducted to look into the performance of Palm Oil Boiler Stone (POBS) as fine aggregate material replacement in concrete. This study presents the results of an experimental investigation carried out to evaluate the mechanical properties of concrete mixtures in which fine aggregate (sand) was partially replaced with POBS. Fine aggregate was replaced with 5% and 10% of POBS by weight. Tests were performed for properties of fresh concrete. Splitting tensile strength and flexural strength were determined at 7, 14 and 28 days. The splitting tensile strength and flexural strength of specimens with 10% POBS content were 15% and 33% respectively, higher than those of the control specimen at 28 days. Test results indicate significant improvement in the strength properties of plain concrete by inclusion of POBS as partially replacement of fine aggregates.